Recombinant BCG expressing the LTAK63 adjuvant induces increased early and long-term immune responses against Mycobacteria - Carvalho Dos Santos, Carina (Hum Vaccin Immunother, 2019)
The development of more effective vaccines against Mycobacterium tuberculosis has become a world priority. Previously, we have shown that a recombinant BCG expressing the LTAK63 adjuvant (rBCG-LTAK63) displayed higher protection than BCG against tuberculosis challenge in mice. In order to elucidate the immune effector mechanisms induced by rBCG-LTAK63, we evaluated the immune response before and after challenge. The potential to induce an innate immune response was investigated by intraperitoneal immunization with BCG or rBCG-LTAK63: both displayed increased cellular infiltration in the peritoneum with high numbers of neutrophils at 24 h and macrophages at 7 d. The rBCG-LTAK63-immunized mice displayed increased production of Nitric Oxide at 24 h and Hydrogen Peroxide at 7 d. The number of lymphocytes was higher in the rBCG-LTAK63 group when compared to BCG. Immunophenotyping of lymphocytes showed that rBCG-LTAK63 immunization increased CD4(+) and CD8(+) T cells. An increased long-term Th1/Th17 cytokine profile was observed 90 d after subcutaneous immunization with rBCG-LTAK63. The evaluation of immune responses at 15 d after challenge showed that rBCG-LTAK63-immunized mice displayed increased TNF-α-secreting CD4(+) T cells and multifunctional IL-2(+) TNF-α(+) CD4(+) T cells as compared to BCG-immunized mice. Our results suggest that immunization with rBCG-LTAK63 induces enhanced innate and long-term immune responses as compared to BCG. These results can be correlated with the superior protection induced against TB.